Contribution of GD2 ganglioside to aggressivness of human cholangiocarcinoma. (March 2023) - Mannini, A.; Raggi, C.; Correnti, M.; Rovida, E.; Aureli, M.; Carsana, E.V.; Piombanti, B.; Pastore, M.; Battula, V.L.; Andersen, J.; Coulouarn, C.; Marra, F.
Abstract : Background: Glycosphingolipids (GSL), a peculiar class of plasma membrane lipids, are prevalently expressed in cancer stem cells (CSC). Gangliosides (GS), sialic acid-containing GSL, regulate the malignant phenotype of several cancers. This study aims to provide a GSL and GS profiling of both stem-like subsets and their parental cells in human CCA. Methods: Stem-like subset was enriched by sphere culture (SPH) in CCA cells (HUCCT1, CCLP1). CCA GS patterns were determined by chromatographic procedures. Identification of GSL and GS molecular species and assessment of GS turnover were evaluated by feeding cells with 3H-sphingosine. GS role was investigated using PPMP, a glucosylceramide synthase inhibitor. FACS-sorted GD2+ SPH cells were examined for stem-like gene expression compared to GD2-SPH. Enzymes of GS biosynthesis were analyzed at different times of spherogenesis. Results: In both CCA lines, compared to monolayers (MON), SPH showed changes in specific sphingolipids (Cer, Gb3, SM), and in the amount of total GS. CCA-SPH showed increase content of GM3 and GD1a, and reduction of GM2, Appearance of GD2 was observed, a finding corroborated by high level expression of GM3 synthase as well as GD3- and GM2/GD2 in CCA-SPH. Sphere-forming ability and expression of CSC-related genes were affected by PPMP. CSC features related on GD2 availability were not dependent on GD2 synthase, but on GD3S, the synthase that provides the precursor (GD3) of ganglioside GD2. We then stably transfected both CCLP1 and HUCCT1 cells with the GD3S gene. GD3S-transfected MON cells showed enhanced sphere-forming ability, superior invasive properties, as well as higher drug resistance when treated with cisplatin and oxaliplatin. Global transcriptomic analysis indicated that GD2+ SPH cells were enriched with CSC-markers in addition to several genes involved in pluripotency, self-renewal, and EMT, compared to GD2-SPH. Notably, expression of GM2/GD2 synthases was significantly expressed in tumor samples compared to paired non-tumoral liver tissue of CCA patients (n=104) and correlated with presence of satellite nodules, lymph node invasion, and recurrence. Conclusions: We show for the first time that the CCA stem-like properties may be associated with GS synthetic pathway and pattern. GS synthases could represent potential markers for CCA.